Modelling Facebook and Outlook Event Attendance Decisions Herding and Coordination Traps - Inchauspe, Julian (Springer Nature, 2021)
Facebook and Outlook have been popular choices for arranging physical attendance of social and business events, with clear advantages emphasised in existing literature, but not free of imperfections. Empirical literature has detected evidence of interdependence among users of these platforms; however, their implications for the possibility of herding traps have been unnoticed. This paper contributes with an original theory that demonstrates that no-attendance or low-attendance traps are a necessary and unavoidable outcome under conditions identified in empirical literature for some events—i.e. events subject to what I call ‘social participation constraints’. The main result is that some potentially desirable meetings are most likely failing to materialise due to the very design of the digital tools. Solutions are proposed to improve their designs to optimise users’ experience. Understanding the mechanism driving herding dynamics and traps that may cause digital tools to fail under interdependence should be of fundamental importance to software designers. This paper offers an accessible, self-contained, compact collection of key results that designers of social media tools and apps can use to enhance users’ experience. It can also be used to enhance business practices that apply to social media environments.